PENGARUH MODAL, JAM KERJA, PENGALAMAN KERJA, TEKNOLOGI TERHADAP PENDAPATAN NELAYAN DI KECAMATAN MELAYA KABUPATEN JEMBRANA - Mahavira, Dominikus I Wayan Devanantha; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 3 (2021): VOL 10 NO 3,MARETI 2021 [ 899 - 1330], 2021)
Indonesia is an archipelago that has a lot of natural resource potential. One of its abundant natural resources is the marine and fisheries sector, however the level of welfare of people in coastal areas generally occupies the lowest strata (poor) compared to other communities on land. The uncertain income of fishermen is closely related to the fish catch. This study aims: (1) To analyze the effect of capital, working hours, work experience and technology simultaneously on fishermen's income. (2) To partially analyze the effect of capital, working hours, work experience and technology on fishermen's income. This research was conducted in Melaya District, Jembrana Regency. Sampling in this study amounted to 71 fishermen, in this study using multiple linear regression analysis techniques. The results of the analysis show that: (1) Capital, working hours, work experience, and technology simultaneously have a significant effect on fishermen's income. (2) Capital and technology partially have a positive and significant effect on fishermen's income, while working hours and work experience partially have no effect on fishermen's income. Keywords: Capital, Working Hours, Work Experience, Technology.